2009
DOI: 10.1007/s12564-009-9023-2
|View full text |Cite
|
Sign up to set email alerts
|

A working memory model applied to mathematical word problem solving

Abstract: The main objective of this study is (a) to explore the relationship among cognitive style (field dependence/independence), working memory, and mathematics anxiety and (b) to examine their effects on students' mathematics problem solving. A sample of 161 school girls (13-14 years old) were tested on (1) the Witkin's cognitive style (Group Embedded Figure Test) and (2) Digit Span Backwards Test, with two mathematics exams. Results obtained indicate that the effect of field dependency, working memory, and mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
1
11
0
3
Order By: Relevance
“…Many recent studies support the notion that working memory is related to arithmetic performance ( Fürst & Hitch, 2000;Heathcote, 1994;Kyoung-Min & So-Young , 2002;Logie, Gilhooly, & Wynn, 1994;Alamolhodaei, 2009), mathematics problem solving (Cary & Carlson, 2001;DeStefano & LeFevre, 2004;Klein & Bisanz, 2000;Seitz & Schumann-Hengsteler, 2000;Swanson, 2004;Swanson & Beebe-Frankenberger, 2004;Alamolhodaei, 2009), and even mathematics anxiety (Ashcraft & Kirk, 2001).For example, studies reported by Adams and Hitch (1998) suggested that mental arithmetic performance relies on the resources of working memory. It seems that a major source of mathematical misunderstanding and errors should be sought in memory transformation and subjective organization (Alamolhodaei, 2009). In addition, Ekbia and Alamolhodaei (2000) reported that schoolboys with higher WM capacity were more successful than those with lower WM in the mathematical problem solving, particularly word problems.…”
Section: Working Memorymentioning
confidence: 91%
See 4 more Smart Citations
“…Many recent studies support the notion that working memory is related to arithmetic performance ( Fürst & Hitch, 2000;Heathcote, 1994;Kyoung-Min & So-Young , 2002;Logie, Gilhooly, & Wynn, 1994;Alamolhodaei, 2009), mathematics problem solving (Cary & Carlson, 2001;DeStefano & LeFevre, 2004;Klein & Bisanz, 2000;Seitz & Schumann-Hengsteler, 2000;Swanson, 2004;Swanson & Beebe-Frankenberger, 2004;Alamolhodaei, 2009), and even mathematics anxiety (Ashcraft & Kirk, 2001).For example, studies reported by Adams and Hitch (1998) suggested that mental arithmetic performance relies on the resources of working memory. It seems that a major source of mathematical misunderstanding and errors should be sought in memory transformation and subjective organization (Alamolhodaei, 2009). In addition, Ekbia and Alamolhodaei (2000) reported that schoolboys with higher WM capacity were more successful than those with lower WM in the mathematical problem solving, particularly word problems.…”
Section: Working Memorymentioning
confidence: 91%
“…Solutions to such problems often require cognitive restructuring. Other researchers have also demonstrated the importance of field dependency in science education and mathematical problem solving, in particular word problems (Alamolhodaei, 2002(Alamolhodaei, , 2009Ekbia & Alamolhodaei, 2000;Johnstone & AI-Naeme, 1991;Witkin & Goodenough, 1981). In a more recent study, with the sample of 161 school girls (13-14 years old), Alamolhodaei (2009) also found that field independent students achieved higher results in both an ordinary mathematical exam and a word problem solving exam.…”
Section: Field Dependence/independence Cognitive Stylementioning
confidence: 99%
See 3 more Smart Citations